Film unframed : a history of Austrian avant-garde cinema - Tscherkassky, Peter; SYNEMA-Gesellschaft für Film und Media; Sixpack Film. (Vienna : SYNEMA-Gesellschaft für Film und Media, 2012)
- "There must be something in the water" / Peter Tscherkassky##- I dream of Austria / Adrian Martin##- Ground survey : an initial mapping of an expanding territory / Peter Tscherkassky##- Countdown to zero : before the avant-garde : Austrian visionary film 1951-1955 / Stefan Grissemann##- The world according to Kubelka / Peter Tscherkassky##- The halted sun of Ferry Radax / Peter Tscherkassky##- Fundamental punk : on Kurt Kren's universal cinema / Stefan Grissemann##- Shadow burns : notes on the film works of Marc Adrian / Norbert Pfaffenbichler##- Expanding cinemas exploding / Hans Scheugl##- The generalist : Ernst Schmidt Jr. / Peter Tscherkassky##- Time slice, space block : the synthetic realities of Viennese filmmaker Hans Scheugl / Stefan Grissemann##- Valie Export : the female body in myriad frames / Maureen Turim##- Two telephone books, a lightbulb and a glass plate : how Maria Lassnig's low-fi animated films influenced an entire generation of animation filmmakers / Maya McKechneay##- The garden of earthly delights : on the films of Dietmar Brehm / Bert Rebhandl##- Lisl Ponger's cinema : the lessons of ignorance / Jonathan Rosenbaum##- Works of dreams and shadows : the films of Peter Tscherkassky / Maureen Turim##- The filmic convulsions of Mara Mattuschka / Christa Blümlinger##- Gustav Deutsch, visual thinker / Livio Belloï##- Reanimator, stutterer, eraser : Martin Arnold and the ghosts of cinema / Steve Anker##- Viva voce : Josef Dabernig's operatic avocations / Andréa Picard##- Weapon of choice : notes on notes on film: or, the man who is Squidward Tentacles : on the works of Norbert Pfaffenbichler / Christoph Huber##- "Is this the precise way that worlds are reborn?" : the films of Siegfried A. Fruhauf / Nicole Brenez##- Michaela Grill : vibrating currents / Steve Bates##- Avant-garde now : notes on contemporary film art / Barbara Pichler##- The framework of modernity : some concluding remarks on cinem
boek